Ulcerated tumor as a form of cecum amebiasis - Estapé, Gonzalo; Croci, Fabio; Gastambide, Carmelo; Pérez Penco, Ernesto; Torterolo, Edgardo (Cirugía del Uruguay, 1983)
A case of amebic ulcerated pseudo-tumor ot tne cecum in a country's patient is presented. The patient was operated on the diagnosis of an appendicular abscess and a right hemicolectomy was performed. The diagnosis was do11e after the histology examination, showed typical amebic trophozoite forms. The evolution was good and specific drug treatment was given.